Preparation and characterization of activated carbon from palm kernel shell - Che Pa, Nasrul Fikry; Chew, Yi Zhong (Penerbit UTHM, 2017)
In Malaysia, the production of activated carbons is still coconut-based although Malaysia has long shifted from coconut into palm oil plantation. Huge amount of waste Palm Kernel Shells (PKS) are being generated and disposed off into the landfill with little known of their usage on large scale. In this study, the potential of production of activated carbon from raw palm kernel shells are studied. Activated carbon was prepared from raw palm kernel shells using chemical activation with potassium hydroxide (KOH) as an activating agent. The effects of different process parameters: KOH concentration, activation temperature and time on physicochemical properties of the prepared activated carbon were investigated. The activated carbon was analyzed using scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), Fourier Transform Infrared (FTIR) spectroscopy, proximate analysis and methylene blue adsorption study. FTIR analysis indicates that raw palm kernel shell has successfully been converted into activated carbon. SEM photograph revealed that prepared activated carbons have numerous burn-off pores with extensive surface area for adsorption. Activated carbon sample prepared at 700 ºC and 1 hour activation with 30 wt % KOH impregnation showed greatest extend of methylene blue removal of 6.932 mg/g equivalent to 69.324 %RE with largest specific surface area of 21.137 x 10-3 km2kg-1 have been reported. This study shows that palm kernel shells can be used as a good source for the production of activated carbon.